Electrical Characteristics of Planar Pbthalocyanine Thin Films - Mohammed, K. A (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The electrical properties of thin film interdigital metalÂ phthalocyanine - metal devices have been studied with regard to purity and electrode material . Devices utilising phthalocyanines ( H2 Pc , NiPc and CuPc) films with Au, Ag , Cu ’ In and AI electrodes have been prepared with Pc layers fabricated from both as - supplied Pc powder and entrainer - subeimed material . The results indicate that sublimed phthalocyanine with gold electrodes offers the best material combination with regard to linearity , reversibility and reproducibility. Measurements of current temperature characteristics of phthalocyanines indicate that the impurity of the film have a major influence on conduction mechanism.